Komparasi Nilai Tukar Petani Perikanan Tangkap dan Perikanan Budidaya di Provinsi Sulawesi Selatan - Amri, Muhammad Irwandhi; Akhmad, Akhmad; Natsir, Mohammad; Sribianti, Irma; Tahir, Ratnawati (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This study compares the economic welfare of farmers in the capture and aquaculture fisheries sectors in South Sulawesi Province through an analysis of Fisherman’s Exchange Rate (NTP) as an indicator of purchasing power and economic stability. Secondary data from the South Sulawesi Central Statistics Agency (BPS) were used to examine the development of farmers' exchange rates in both sectors between 2018 and 2022. Statistical analysis shows that the NTP in the capture fisheries sector is higher than in aquaculture, indicating relatively better welfare in the capture sector. Results from a paired sample t-test reveal a significant difference between the two sectors (p < 0.001), with a more stable average NTP in the capture sector. This study recommends technological and infrastructure support for the aquaculture sector to improve economic stability. The study has implications for more adaptive and sustainable fishery management policies to enhance the welfare of fishery farmers in South Sulawesi.